IMPLEMENTATION OF LOCAL DIAGNOSTIC REFRENCES LEVEL (DRL) ON CT-SCAN AT RSI YOGYAKARTA PDHI - Mas’uul, Ali Roo’in; Kanayanaquita; Handayani, Nita (Jurnal Kesehatan, 2025)
One of the parameters of CT-Scan that is of particular concern is the radiation dose. Receipt of excessive radiation dose in patients will cause cancer. It is necessary to minimize the radiation dose received by patients in each examination by comparing the optimization index called Diagnostic Reference Level (DRL). This study aims to determine the local DRL value on CT-Scan at RSIY PDHI and compare and analyze with the national DRL value set by BAPETEN. This research is quantitative study with an experimental approach that aims to analyze the CTDIvol and DLP values on CT-Scan at RSIY PDHI. The DRL value is determined by determining the 75thpercentile value of CTDIvol and DLP values in CT-Scan examinations. This study was conducted on head examination in 156 patients without contrast and 2 patients with contrast, abdominal examination in 54 patients without contrast and 7 patients with contras, and thorax examination in 2 patients without contrast and 1 patient with contrast. In this study, the local DRL value of RSIY PDHI was obtained, with CTDIvol values in head, abdomen, and thorax examinations without contrast of 55,1; 12,5; and 5,4 mGy, respectively. And examination without contrast obtained values of 38,4; 10,2; and 4,47 mGy respectively. The DLP values in head, abdomen, and thorax examinations without contrast are 1122; 601; and 150 mGy.cm respectively. Examination with contrast obtained respectively 781; 479; and 151 mGy.cm. The DRL value obtained is categorized as safe because the local DRL value of RSIY PDHI has a lower value than the national DRL value set by BAPETEN.